Unraveling paediatric constipation: a biopsychosocial approach toward a 2-year-old’s chronic gastrointestinal quandary (UCC Student Medical Journal, 2024)
Introduction:This case report unfolds the diagnostic and therapeutic journey of a 2-year-old girl with chronic constipation unresponsive to conventional laxatives, hinting at a possible underlying organic pathology amidst a complex familial and personal medical background.Methods:Utilizing a biopsychosocial model, a comprehensive assessment was conducted to delineate the predisposing, precipitating, perpetuating, and protective factors affecting the patient’s gastrointestinal health. A multidisciplinary approach was employed to craft a tailored management plan involving the patient and her parents.Results:The application of the biopsychosocial model unveiled an intricate interplay of biological,psychological, and social factors contributing to the patient’s persistent constipation. The multidisciplinary approach fostered a nuanced understanding and a patient-centered management plan, addressing not only the gastrointestinal symptoms but also the broader health and well-being of the child and her family.Discussion:The case accentuates the essentiality of transcending traditional biological examinations, embracing a holistic, patient-centered, biopsychosocial model, especially in pediatric patients with complex medical and familial backgrounds. It also underscores the need for an integrated, multidisciplinary approach for effective diagnosis and management in complex pediatric gastroenterological cases.Conclusion:The case elucidates the paramountcy of a multidisciplinary, biopsychosocial approach in navigating complex pediatric gastroenterological cases, fostering an enriched discourse on patient-centered care and enhancing long-term health outcomes.